2022
DOI: 10.7759/cureus.21616
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide Overdose-Induced Acute Pancreatitis

Abstract: Liraglutide, a long-acting cardioprotective glucagon-like peptide (GLP)-1 analog, is effective for medical weight loss and glycemic control in type 2 diabetes. It is generally well tolerated with mild side effects. There are few reports on complications from Liraglutide overdose. The aim of this paper is to report the case of a 25-year-old healthy female who presented with acute pancreatitis secondary to Liraglutide overdose and to review the current literature on Liraglutide used for obesity management. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…This is consistent with the increased risk of acute pancreatitis with DPP-4 inhibitors reported by Doni et al (Doni et al, 2022). It has previously been reported that GLP-1RA may cause acute pancreatitis (Smits and Van Raalte, 2021;AlSaadoun et al, 2022), but two recent network meta-analyses revealed that DPP-4 may increase the risk of acute pancreatitis, while GLP-1RA seems to have no effect (Kanie et al, 2021;Zhuo et al, 2021). However, there are no reports indicating whether the combination of GLP-1RA with SGLT-2i increases this risk.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with the increased risk of acute pancreatitis with DPP-4 inhibitors reported by Doni et al (Doni et al, 2022). It has previously been reported that GLP-1RA may cause acute pancreatitis (Smits and Van Raalte, 2021;AlSaadoun et al, 2022), but two recent network meta-analyses revealed that DPP-4 may increase the risk of acute pancreatitis, while GLP-1RA seems to have no effect (Kanie et al, 2021;Zhuo et al, 2021). However, there are no reports indicating whether the combination of GLP-1RA with SGLT-2i increases this risk.…”
Section: Discussionsupporting
confidence: 89%
“…Liraglutide may also contribute to an increased risk of acute gallbladder or biliary disease. 168 , 169 …”
Section: Signaling Pathways Driving Nafl/nash Development and Related...mentioning
confidence: 99%
“…However, the use of LIRA faces challenges, especially with regard to adverse effects, such as nausea and diarrhea, in addition to causing liver and pancreatic problems [10][11][12]. There is also a need for administration by daily subcutaneous injection, which may impact treatment adherence [13].…”
Section: Introductionmentioning
confidence: 99%